Predisposição para Formação de Capital Social entre Comerciantes dos Corredores Comerciais da Região Central do Município de São José dos Campos - SP - Monica Franchi Carniello (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2011)
Cooperation, one element that results in the formation of social capital of an individual or group of individuals, is one of the variables of interference in local development process. The aim of this paper is to verify the disposition to perform actions of promotion and marketing communication in a cooperative manner by traders in the central region of São José dos Campos -SP, in order to foster the development of local commerce. The research is characterized as exploratory, qualitative approach to data collection documents. It was found that there is a clear predisposition for cooperation on the part of traders in the corridors studied, which is a potential for the formation and accumulation of social capital and therefore an advantage for the development of local trade.